Interleukins-27 Aggravates Liver Injury by Impairing the Antimicrobial Response of Macrophages via the Promotion of Mitochondrial Dysfunction in the Context of Sepsis - Yuehua You; Yuyan Li; Lin Ye; Fang Xu; Jing Fan (Mediators of Inflammation)
Conclusions: These findings indicated that IL-27 impairs the bacterial phagocytosis capacity of macrophages by aggravating mitochondrial dysfunction to aggravate AHI during sepsis.